2016
DOI: 10.1111/jnc.13753
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in cardiolipin decreases mitochondrial spare respiratory capacity and increases glucose transport into and across human brain cerebral microvascular endothelial cells

Abstract: Microvessel endothelial cells form part of the blood-brain barrier, a restrictively permeable interface that allows transport of only specific compounds into the brain. Cardiolipin is a mitochondrial phospholipid required for function of the electron transport chain and ATP generation. We examined the role of cardiolipin in maintaining mitochondrial function necessary to support barrier properties of brain microvessel endothelial cells. Knockdown of the terminal enzyme of cardiolipin synthesis, cardiolipin syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…In addition, the presence of abundant glucose in the culture medium, combined with a minimal demand for "work", may mask the effects of Ptd 2 Gro loss on substrate utilization, fat accumulation, or glucose disposal. We recently showed that a reduction in Ptd 2 Gro in human brain endothelial HCMEC/ D3 cells led to increased glucose uptake and glycolysis [20]. In summary, we show that BTHS lymphoblasts exhibit increased glucose uptake and TAG synthesis from glucose.…”
Section: Resultssupporting
confidence: 58%
“…In addition, the presence of abundant glucose in the culture medium, combined with a minimal demand for "work", may mask the effects of Ptd 2 Gro loss on substrate utilization, fat accumulation, or glucose disposal. We recently showed that a reduction in Ptd 2 Gro in human brain endothelial HCMEC/ D3 cells led to increased glucose uptake and glycolysis [20]. In summary, we show that BTHS lymphoblasts exhibit increased glucose uptake and TAG synthesis from glucose.…”
Section: Resultssupporting
confidence: 58%
“…Thus, reduction in the cardiolipin content decreases SRC levels. 8 In line with this, mild uncoupling resulting in a moderate increase in proton permeability leading to a reduction in ROS production without affecting ATP levels could decrease SRC levels, probably by increasing basal respiration. 8,9…”
Section: Src Depends On the Integrity Of The Mitochondrial Electronmentioning
confidence: 80%
“…7 One should note that FCCP concentration needs further dose optimization studies. Optimal FCCP doses to obtain SRC depend on experimental parameters such as temperature 8 and excessive uncoupling promotes ROS-dependent cell death and eventually energetic crisis. 9 Because optimal doses can vary according to the different experimental conditions, it is better to do sequential additions of uncouplers to achieve maximal rate ( Figure 1).…”
Section: Respiratory Capacit Ymentioning
confidence: 99%
“…It has been demonstrated that cardiolipid synthase knockdown significantly decrease the capacity of spare respiration, but does not affect the activity of complex I in hCMEC/D3 cells. The possible compensatory mechanism might be associated with increased utilization of glucose, as shown by increased glycolysis and increased activity of pyruvate kinase and GLUT1, which are correlated with inactivation of GSK-3β [48]. GSK-3β inactivation or GSK-3β-Ser9 phosphorylation maintains the efficiency of oxidative phosphorylation (OXPHOS) and controls the production of ROS.…”
Section: Gsk-3β Regulates Mitochondrial Bioenergeticsmentioning
confidence: 99%